High-speed forging of hollow metal powder preforms - Agrawal M.; Jha A.K.; Kumar S. (My University, 2025)
This paper discusses about the various technological aspects of a high-speed forging of sintered copper powder hollow discs. Experiments are conducted and measurements are made in the development of barrelling, strain variations at the free surface and densification during dry and lubricated high-speed forging of sintered copper powder hollow discs at room temperature. The relationship between the frictional stress at the interface and other process variables is discussed and an analysis has been done for the estimation of pressure distribution by the solution of the equations of equilibrium taking barelling into consideration for axial symmetry sinter-forging condition. Results are discussed critically to illustrate the interaction of various processing parameters involved during high-speed forging of hollow sintered preform discs and are presented graphically.